SAUDADE AND NOSTALGIA: PASSIONATE CONFIGURATIONS OF MISSING IN MARIA BETHÂNIA’S CONCERT ROSA DOS VENTOS - Junior, Renato Forin (2012)
Saudade and nostalgia are passions that sometimes demonstrate an indistinct character. This paper seeks to find, in semiotic approach, tools that clarify the passionate configurations of these feelings so widespread in the Portuguese language and less studied by theory of meaning. From the definitions of lexemes, etymological research and finally the semiotic modalization analysis, this work establishes the main differences between these two words that describe the feelings of missing. Such soul conditions appear; in general, in individuals deprived from having an object-value, which produces dysphoric state. The passionate speech reflects, then, modals impasses of a "desire to be together", in spite of the impossibility. Nostalgia is characterized as a specific form of saudade. For a more practical understanding of these conceptual boundaries – besides mentioning a variety of literary and journalistic texts – the article evokes parts of the Rosa dos ventos concert, starring Maria Bethânia in 1971. During the military dictatorship, the feeling of saudade of exiled politicians was sung in the concert through a script composed with poems and songs.